2022
DOI: 10.29138/ijebd.v5i6.2070
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Female Entrepreneurship Pre-, During- and Post-Covid-19 Prospects in South Africa

Abstract: Purpose: Female entrepreneurship discourse continues to receive heightened attention owing to various factors including the value of their contribution to national socioeconomic development. While the patriarchal nature of African societies remains one of the major issues impacting female entrepreneurs, the Covid-19 pandemic exacerbated the situation, therefore necessitating research that addresses interventions. This study examined the challenges of female entrepreneurship before, during, and the post-Covid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Moreover, the study demonstrated that using EC as a system of support for women entrepreneurs can increase their ESE (Yusuff, et al, 2019). The key results are that, despite the difficulties faced by women entrepreneurs, the South African governments have over the years prioritized the growth of those deemed to have previously been disadvantaged, particularly women entrepreneurs and that customised EC provided opportunities for women entrepreneurs to advance their knowledge and technical skills (Rudhumbu, et al, 2020;Iwu et al, 2022). Considering the importance of entrepreneurship coaching as a learning technique and support function once more about the difficulties and opportunities facing women entrepreneurs (Rudhumbu, et al, 2020;Iwu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study demonstrated that using EC as a system of support for women entrepreneurs can increase their ESE (Yusuff, et al, 2019). The key results are that, despite the difficulties faced by women entrepreneurs, the South African governments have over the years prioritized the growth of those deemed to have previously been disadvantaged, particularly women entrepreneurs and that customised EC provided opportunities for women entrepreneurs to advance their knowledge and technical skills (Rudhumbu, et al, 2020;Iwu et al, 2022). Considering the importance of entrepreneurship coaching as a learning technique and support function once more about the difficulties and opportunities facing women entrepreneurs (Rudhumbu, et al, 2020;Iwu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is a methodical approach to finding, gathering, and analysing literature regarding a specific topic to better identify any trends that could be interpreted about the phenomenon (Kazumi & Kawai, 2017). The strength of this strategy is that the author may carefully select publications that communicate different points of view from a body of literature (Iwu, Sibanda & Makwara, 2022). To carefully find, evaluate, and analyze relevant studies on entrepreneurial coaching and entrepreneurial self-efficacy, particularly in the context of women's entrepreneurship, the author employed the descriptive literature review technique for this study.…”
Section: Methodsmentioning
confidence: 99%